Information System Optimization: Accounting, Remuneration, and Tax Compliance Perspectives - Aulia Rachman, Helmy; Dimar Alam, Muhammad; Hazbiy Shaffan, Nur (Research Horizon, 2025)
This study discusses the influence of accounting information systems, satisfaction with remuneration, and satisfaction with taxation on the performance of lecturers and employees at Brawijaya University. The urgency of this study is motivated by the phenomenon of a new system at the University, namely UB Satu Data, which can support the performance of lecturers and employees in terms of accounting information systems, remuneration systems, and also taxation. The purpose of this study is to measure the influence of accounting information systems, satisfaction with remuneration, and satisfaction with taxation policies on the performance of lecturers and employees at Brawijaya University. The research method used is quantitative with a comparative causal research type using a survey of all employees and lecturers at Brawijaya University. The results of this study indicate that a good remuneration system can improve job satisfaction and performance of lecturers and educators through financial and moral rewards. Satisfaction with taxation policies such as transparency and administrative efficiency have a significant effect on performance with a coefficient of 0.527 (p = 0.009). Changes to PP No. 58 of 2023 affects the calculation of PPh 21 tax, increases taxpayer compliance but raises concerns regarding administration and net income. Institutional support for a transparent tax system affects subjective norms and academic productivity.